PENGARUH KUALITAS PRODUK, INOVASI PRODUK DAN DIGITAL MARKETING TERHADAP KEPUTUSAN PEMBELIAN PADA ANGELO STORE UBUD BALI - Pande Rantika Juli; I Nengah Suardhika; Gede Yudhi Hendrawan (VALUES, 2021)
The phenomenon of competition in the era of globalization will increasingly direct the country's economic system and market mechanisms, which in turn will position marketers to always develop in grabbing market share. In implementing good marketing, producers must know what the needs and desires of consumers are, so that the products offered will be in accordance with consumer demand. This study aims to determine and explain the effect of product quality, product innovation and digital marketing on consumer purchasing decisions at Angelo Store Ubud Bali. The number of samples in this study were 90 employees who were determined by purposing sampling method. The collected data were analyzed using multiple linear regression. The results of the analysis found that product quality, product innovation and digital marketing have a positive effect on consumer purchasing decisions at Angelo Store Ubud Bali. This research is further expected to develop research using other variables which theoretically can influence purchasing decisions.